The Analisa Scouring pada Bagian Bawah Jembatan, pada Rencana Pembangunan Jembatan Besi 2, Kabupaten Tenggarong, Kalimantan Timur - Barus, Freddy; Dhiana dwi widiawati; Insan Kamil; Tommy E. Sutarto; M. Ilham Taufik; M. Fiki Alimul (Teknika, 2026)
Tenggarong City is located between 116˚47 BT – 117˚04 BT and 0˚21 LS – 0˚34 LS on the banks of the Mahakam River, requires a bridge to connect areas that are separated, particularly by the river. Currently, there are several connecting bridges in Tenggarong City, including an iron bridge that is 37 metres long and 6 metres wide. The current condition of the bridge is considered alarming, as evidenced by the presence of holes on several sides and floodwaters that almost reach the bridge floor, raising concerns about the safety of users. This condition requires the construction of a second iron bridge 100 metres from the existing bridge. In bridge design, consideration must be given to scouring of the bridge substructure. The analysis conducted was a hydrological, sediment transport and scouring analysis, which yielded 50-year return period design discharge of 801.9 m3/sec, with maximum water level of 5.24 metres. The scouring analysis results using the HEC-RAS program showed scouring of 5.01 metres at STA 808.98, 4.73 metres at STA 559.1, and 5.24 metres at STA 503.18. Scouring control is carried out using protective wing plates and constructing protective riprap around bridge pillars so that damage to the bridge's substructure can be anticipated.